Modernizing Government IT Systems: A Case Study on Enhancing Operational Efficiency and Data Integrity - Duvvur, Vijayasekhar (International Journal of Computational and Experimental Science and Engineering, 2025)
This case study explores the modernization of a government IT system that had been operational for over two decades, addressing critical challenges related to efficiency, scalability, and security. The transformation involved AI-driven process automation, cloud migration, and advanced cybersecurity measures to enhance operational efficiency and data integrity. Key enhancements included automated data validation, AI-powered system monitoring, and predictive maintenance, significantly reducing manual intervention and system downtime. A structured cloud transition was executed to ensure seamless data migration, improving real-time accessibility and interoperability across agencies. The modernization led to a 60% reduction in manual processes, 70% lower downtime, and a 42% decrease in operational costs, creating a more resilient and future-ready IT infrastructure. This study highlights how leveraging AI and cloud technologies can transform legacy systems, ensuring higher efficiency, security, and regulatory compliance. The findings serve as a blueprint for organizations seeking to modernize aging IT infrastructure while ensuring long-term sustainability and efficiency.